2014
DOI: 10.5992/ajcs-d-14-00021.1
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Palsy following Mandibular Setback: A Case Report and Review of the Literature

Abstract: Introduction: Mandibular prognathism is a common dentofacial deformity that is often treated with orthognathic surgery (jaw straightening or corrective jaw surgery). The two most common types of operations to correct mandibular prognathism are the mandibular bilateral sagittal split osteotomy (BSSO) and/or the intraoral vertical ramus osteotomy (IVRO). Although there are other surgeries that exist to correct this type of deformity, the BSSO and IVRO are the most commonly used treatment options. The advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Recently, Shimada et al [4] reported cases of facial nerve palsy after bilateral sagittal split ramus osteotomy, most of which developed within 3 days after surgery. Several factors can cause facial nerve damage during or after reduction mandibuloplasty, including the compression of nerves by retractors, postoperative edema or hematoma, pressure packing in the retromandibular region, and unusual fractures of the mandible or styloid process [4][5][6][7][8][9]. However, this case suggests that, to avoid facial nerve injury, blinded hemoclips should not be used.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Shimada et al [4] reported cases of facial nerve palsy after bilateral sagittal split ramus osteotomy, most of which developed within 3 days after surgery. Several factors can cause facial nerve damage during or after reduction mandibuloplasty, including the compression of nerves by retractors, postoperative edema or hematoma, pressure packing in the retromandibular region, and unusual fractures of the mandible or styloid process [4][5][6][7][8][9]. However, this case suggests that, to avoid facial nerve injury, blinded hemoclips should not be used.…”
Section: Discussionmentioning
confidence: 95%
“…2,3 The Hunsuck-Epker (HE) approach requires dissecting muscle attachments and invading into the oral soft tissue up to the lingula area. 2 However, the HE technique has been reported to cause facial nerve disturbance 4,5,6 and increase the potential risk of compromised airways after a mandibular setback procedure on a severe skeletal Class III deformity. 7 Low Z technique was introduced in 2016 8 and recently developed into a novel modification of the 1 Low Z plasty (NM-Low Z) technique 9 at our hospital.…”
Section: Introductionmentioning
confidence: 99%